Alternatif, Penyelesaian Sengketa Utang Piutang berbasis Aplikasi Online - Rahmat Bakhtiar Pratama; Hendra Djaja; Tri Susilaningsih; Moh Fahrial Amrullah (Bhirawa Law Journal, 2020)
Debt receivables are based on an agreement, an agreement on receivables is included in the principal agreement. In the event of a process of debt receivable agreement made by the creditor and debtor. debtor basically based on trust between the creditor and the debtor, but a lot of debt occurs using additional agreements or assessors that govern collateral, accounts receivable debtusing collateral can vary, collateral for movable or immovable objects, tangible movable objects or intangible. The phenomenon that is happening right now is that there are accounts receivable debts where the lenders and debt recipients have never met, these debts use online applications or commonly referred to as online applications and some call it the term fintech which stands for financial technology. This debt continues to use the agreement, and the agreementshould still comply with the rules and regulations which are basically regulated in article 1313 BW, and 1320 BW. Problems occur if one of the parties in the debt agreement is broken or promised to commit an act against the law, disputes that occur in the event of the debt can be resolved by resolving disputes outside the court. Settlement of disputes outside the court can bean alternative to problems that occur in the debt and credit activities using online applications.